The Comparison in Countries Obedience on CPIA Implementation through Country’s Governance: A Case Study of Europe and Central Asia - Nabilah, Konita Ayu; Zahidi, M. Syaprin; Suhermanto, Dedik Fitra (Srawung: Journal of Social Sciences and Humanities, 2022)
The International Development Association (IDA) is part of the World Bank Group that helps the poorest countries reduce poverty by providing concessional loans and grants for programs aimed at boosting economic growth and improving living conditions. Through the CPIA Exercise, the country will be assessed from the extent to which a government policy can encourage a country's development. That way, conducting a review of the parliamentary system and the form of the country will be able to provide an overview of how the performance of a country in the policy-making process by the government can influence the activities of the CPIA. The researcher will use the comparative political MSSD method to find out how the condition of a domestic government can affect domestic development, where it is found that the similarity of the parliamentary system and form of government does not ensure that a country will get the same results due to different domestic conditions. There are two objectives of this research, there are (1) to provide an overview of how the performance of a country in the policy-making process by the government can influence the activities of the CPIA: and (2) to find out how the condition of a domestic government can affect domestic development.